2014
DOI: 10.1002/oby.20901
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiles and childhood obesity

Abstract: Objective To identify metabolite patterns associated with childhood obesity, to examine relations of these patterns with measures of adiposity and cardiometabolic risk, and to evaluate associations with maternal peripartum characteristics. Design and Methods We employed untargeted metabolomic profiling to quantify metabolites in plasma of 262 children (6–10 years). We used principal components analysis to consolidate 345 metabolites into 18 factors and identified two that differed between obese (BMI ≥95%ile;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
168
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(190 citation statements)
references
References 37 publications
19
168
3
Order By: Relevance
“…Although MSC were selected based on maternal prepregnancy BMI, there was great heterogeneic overlap in adiposity and maternal FFA concentrations between the OB and NW groups. We therefore tested relationships using both groups combined (when the phenotypic variable was continuous) and also within OB offspring specifically, as this is the group with the highest risk for metabolic derangements as children (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MSC were selected based on maternal prepregnancy BMI, there was great heterogeneic overlap in adiposity and maternal FFA concentrations between the OB and NW groups. We therefore tested relationships using both groups combined (when the phenotypic variable was continuous) and also within OB offspring specifically, as this is the group with the highest risk for metabolic derangements as children (16).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in adipocytes from OB adults, there is decreased fatty acid oxidation, increased lipogenesis, and spared amino acid catabolism (13,20,21). Biomarkers for these processes can be observed in plasma of OB school-aged children (16,22,23), suggesting early changes in mitochondria metabolism in established obesity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study sample for this analysis comprised 126 of 262 mother-child pairs from a published study on mid-childhood metabolite patterns, obesity, and metabolic risk (10). The only inclusion criteria for the present study was available cord blood for the metabolomics assays (≥50 uL; n = 126).…”
Section: Methodsmentioning
confidence: 99%
“…Metabolomics analyses in children have found that higher circulating branched chain amino acids (BCAAs) are associated with obesity status (10, 11), as well as subclinical risk factors for metabolic disease like insulin resistance (10, 12). Studies in adults have shown that elevations in serum branched chain amino acids (BCAAs) are detectable several years prior to development of insulin resistance and incident type 2 diabetes (13, 14), even among individuals of similar weight status (13).…”
Section: Introductionmentioning
confidence: 99%